On elastic metal-to-metal vacuum seals - Inbar, A (Vacuum, 1972)
An analysis of the sealing behaviour of elastic metal-to-metal vacuum seals is given. The analysis is based on the Hertz formulae for the contact stresses between curved elastic surfaces. Formulae and nomographs, for the leak rate as a function of the sealing force in the elastic range, are derived.